Screening the Marquis de Sade pleasure, pain and the transgressive body in film - Hallam, Lindsay Anne, 1979- (McFarland & Co., Inc., 2012)
"Since its publication, the works of the Marquis de Sade have challenged the reading public with a philosophy of relentless physical transgression. This is the first book-length academic study by a single author that applies the philosophy of the Marquis de Sade to the analysis of a wide array of film texts"--Provided by publisher.